Rimpu Culture as a Means of Instilling Islamic Character Values at Madrasah Aliyah Environment (EDUKASIA, 2025)
This study aims to analyze the Rimpu culture as a means of instilling Islamic character values in students at Madrasah Aliyah environment. The location of the study was at the Madrasah Aliyah in Bima City, West Nusa Tenggara. This study used a descriptive qualitative method with data collection using observation, interview, and documentation instruments. The collection technique was carried out in four stages, namely: data collection, data reduction, data presentation, and verification (drawing conclusions). The results of this study indicated that the application of local culture to instill the Islamic character values is still rarely used in the Madrasah Aliyah environment. In this case, the Rimpu culture can be an effective means for optimizing the instillation of Islamic character values at Madrasah Aliyah environment. The Rimpu culture is a traditional dress of the Bima community which is worn to cover the entire body. The Islamic values covered by the Rimpu culture are such as; obedience to Allah's commands, the obligation to cover the genitals, politeness and shame, as well as simplicity and sincerity. The instillation of Rimpu cultural values in the Madrasah Aliyah environment can be done by integrating it into the education curriculum, extracurricular activities, holding religious and cultural events, and schools making policies that support Rimpu culture in instilling Islamic character values in students  at Madrasah Aliyah environment.